2014
DOI: 10.1111/boj.12170
|View full text |Cite
|
Sign up to set email alerts
|

Seedling mycorrhiza: a discussion of origin and evolution in Orchidaceae

Abstract: Recent phylogenetic analyses confirm the monophyly of Orchidaceae as sister group to the remainder of Asparagales, and identify the sequence of early branching lineages in Orchidaceae. Orchid seedling mycorrhiza (OSM) involving rhizoctonious fungi is distributed widely in all subfamilies, including the first branching ones, and its status as a founding event is thus supported. OSM is recognized as one element in the character syndrome that distinguishes orchid biology, and we argue that OSM was the first to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 102 publications
(76 reference statements)
2
47
0
Order By: Relevance
“…and Taeniophyllum obtusum ( Irawati, 2009 ). Our verification of Ceratobasidium from D. lindenii in South Florida lends support for Yukawa’s view (2009) that members of the Ceratobasidiaceae are linked to orchids in the Vandeae tribe, especially the Angraecinae subtribe, by a ‘phylogenetic signal’ ( Yukawa et al , 2009 ; Rasmussen and Rasmussen, 2014 ). Furthermore, Chomicki et al (2014) found mycorrhizal structures (pelotons) in various states of digestion in adult ghost orchid roots, and a specialized mechanism for restricting fungal growth in the lower cortex without reducing photosynthesis in the upper root layer, thereby maximizing carbon gain.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…and Taeniophyllum obtusum ( Irawati, 2009 ). Our verification of Ceratobasidium from D. lindenii in South Florida lends support for Yukawa’s view (2009) that members of the Ceratobasidiaceae are linked to orchids in the Vandeae tribe, especially the Angraecinae subtribe, by a ‘phylogenetic signal’ ( Yukawa et al , 2009 ; Rasmussen and Rasmussen, 2014 ). Furthermore, Chomicki et al (2014) found mycorrhizal structures (pelotons) in various states of digestion in adult ghost orchid roots, and a specialized mechanism for restricting fungal growth in the lower cortex without reducing photosynthesis in the upper root layer, thereby maximizing carbon gain.…”
Section: Discussionsupporting
confidence: 80%
“…Ceratobasidiaceae members are known to promote seed germination in a wide range of orchid subfamilies, specifically Apostasiodeae, Vanilloideae, Epidendroideae, Orchidoideae ( Dressler, 1993 ; Rasmussen et al , 2015 ) and Vandeae ( Irawati, 2009 ; Rasmussen and Rasmussen, 2014 ). Currently, there is only one published study on Thanatephorus (Ceratobasidiaceae) germination promotion capacity in seeds of Taeniophyllum obtusum , also a leafless orchid species ( Irawati, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The identity of OrM symbionts of adult plants largely depends on the identity and habitat of the orchid host (Dearnaley et al, 2012). In particular, photosynthetic orchids in sunny grassland habitats mainly associate, both as seedlings and as adult plants, with fungi in the 'rhizoctonia' complex sensu lato (Smith & Read, 2008;Dearnaley et al, 2012;Rasmussen & Rasmussen, 2014), a polyphyletic assemblage encompassing Agaricomycetes belonging to the Serendipitaceae (Sebacinales; Weiß et al, 2016), Ceratobasidiaceae and Tulasnellaceae (Roberts, 1999;Taylor et al, 2002;Weiß et al, 2004). The Tulasnellaceae, in particular, are the most frequently found OrM fungi in both temperate and tropical regions (Dearnaley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…By forming obligate relationships with compatible fungi, orchid hosts gain carbon, nutrients, and water at one or more life history stages 13,27 . The majority of orchids associate with fungal taxa belonging to the polyphyletic/“rhizoctonia” group of Basidiomycetes, specifically Ceratobasidiaceae, Serendipitaceae (Sebacinales), and Tulasnellaceae 13,28,29 . Identifying specific OMF may be advantageous for orchid conservation—e.g., orchid propagation, ex situ seeding, seedling translocation—as contrasting fungal taxa may differ in nutrient uptake efficiency or stimulation of germination 3033 .…”
Section: Introductionmentioning
confidence: 99%